2014
DOI: 10.1186/1471-2393-14-272
|View full text |Cite
|
Sign up to set email alerts
|

Association between gestational age at birth, antenatal corticosteroids, and outcomes at 5 years: multiple courses of antenatal corticosteroids for preterm birth study at 5 years of age (MACS-5)

Abstract: BackgroundThe Multiple Courses of Antenatal Corticosteroids for Preterm Birth Study (MACS) showed no benefit in the reduction of major neonatal mortality/morbidity or neurodevelopment at 2 and 5 years of age. Using the data from the randomized controlled trial and its follow-up, the aim of this study was to evaluate the association between gestational ages at birth in children exposed to single versus multiple courses of antenatal corticosteroid (ACS) therapy in utero and outcomes at 5 years of age.MethodA tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 15 publications
(19 reference statements)
2
67
0
2
Order By: Relevance
“…This may explain the correlation between the use of antenatal corticosteroids and mental development. However, Asztalos et al demonstrated that, in preterm infants, the neurodevelopmental outcome remained the primary factor (such as gestational age at birth), which was contributory regardless of the number of courses of antenatal synthetic corticosteroid therapy [33]. Dexamethasone is not only used to promote fetus lung maturation but also to prevent further intraventricular hemorrhaging in preterm births before 34 weeks’ gestation [34].…”
Section: Discussionmentioning
confidence: 99%
“…This may explain the correlation between the use of antenatal corticosteroids and mental development. However, Asztalos et al demonstrated that, in preterm infants, the neurodevelopmental outcome remained the primary factor (such as gestational age at birth), which was contributory regardless of the number of courses of antenatal synthetic corticosteroid therapy [33]. Dexamethasone is not only used to promote fetus lung maturation but also to prevent further intraventricular hemorrhaging in preterm births before 34 weeks’ gestation [34].…”
Section: Discussionmentioning
confidence: 99%
“…Recommended treatment courses include two doses of 12mg betamethasone administered intramuscularly 24 hours apart or four doses of 6mg dexamethasone administered intramuscularly every 12 hours. This treatment is not standardized across the United States and treatment courses may be administered multiple times 6 , despite recent evidence that suggests that multiple doses of antenatal sGC do not significantly improve clinical outcomes 7 . In fact, the Multiple Courses of antenatal corticosteroids for preterm birth study at 5 years of age (MACS-5 study) indicated that multiple courses of antenatal sGC may have an increased risk for neurodevelopmental and neuropsychiatric conditions at the age of five years providing evidence against the use of multiple courses 7 .…”
Section: Clinical Use Of Antenatal Synthetic Glucocorticoid Therapymentioning
confidence: 99%
“…38 A rescue dose of steroids is often used in these situations; however, multiple courses of ANCS are not recommended due to poor fetal head growth and increased risk of neurodevelopmental impairment by 5 years. [39][40][41] To fully implement ANCS to the greatest benefit of the preterm pregnancies at risk of imminent delivery, improved methods of preterm birth prediction are needed. 42,43 Furthermore, if ANCS treatment is extended from 34 to <37 weeks and many of these fetuses deliver at term, the effects are unknown.…”
Section: A N U S C R I P Tmentioning
confidence: 99%